Experimental acrylonitrile butadiene styrene and polyamide evisceration implant: a rabbit clinical and histopathology study - Gomes Júnior,D.C. (2016)
ABSTRACT The purpose of this study was to evaluate acrylonitrile butadiene styrene (ABS) and polyamide implants in rabbits submitted to evisceration at the macroscopic and microstructure level and to assess clinical response and histopathological changes as well. For the experimental study implants of 12mm diameter were prepared by rapid prototyping, weighed and the outer and inner surfaces evaluated macroscopically and by electron microscopy. In addition, a compression test was performed and ultrastructural damage was then determined. After evisceration of the left eyeball, nine New Zealand rabbits received ABS implants and nine others received polyamide implants. The animals were assessed daily for 15 days after surgery and every seven days until the end of the study (90 days). Histopathological evaluation was performed at 15, 45 and 90 days after surgery. The ABS implants weighed approximately 0.44g, while the polyamide ones weighed 0.61g. Scanning electron microscopy demonstrated that the ABS implants had regular-sized, equidistant micropores, while the polyamide ones showed micropores of various sizes. The force required to fracture the ABS implant was 14.39 ±0.60 Mpa, while for the polyamide one, it was 16.80 ±1.05 Mpa. Fifteen days after surgery, we observed centripetal tissue infiltration and scarce inflammatory infiltrate. Implants may be used in the filling of anophthalmic cavities, because they are inert, biocompatible and allow tissue integration.